1997
DOI: 10.1029/97rs01194
|View full text |Cite
|
Sign up to set email alerts
|

A long‐term investigation of the HF communication channel over middle‐ and high‐latitude paths

Abstract: Abstract. A study of HF communication link and network availability has been carried out using frequency modulated continuous wave (FMCW) swept-frequency sounders operating in an oblique-incidence configuration. The sounder deployment enabled 28 middle-and high-latitude paths to be evaluated; the time period of the study was from December 1994 until the summer of 1996. Propagation conditions including ionospheric mode information, maximum observable frequencies, signal-to-noise ratios, and channel availabiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…For this study, the monthly observed sunspots for years (2000) and (2010) occurs between two points [10].…”
Section: Test and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study, the monthly observed sunspots for years (2000) and (2010) occurs between two points [10].…”
Section: Test and Resultsmentioning
confidence: 99%
“…This result from the fact that as the MUF signals increases it will pass through more layers and communication is lost, because the MUF signals eventually traveling into outer space. As it passes through one layer it may be that then propagates over a greater distance than is required [10].…”
Section: Radio Waves Communicationmentioning
confidence: 99%
“…The availability (and the similar term reliability) is frequently used in the literature referring to the probability for a circuit to achieve a specified performance or a minimum SNR to enable a given quality of service (see, for example, Goodman et al [1997]). In our case, however, the physical layer for data transmission is not yet defined and therefore the required SNR to offer a given service is unknown.…”
Section: Link Availabilitymentioning
confidence: 99%
“…Abnormal propagation at elevated HF bands caused by Es patches was shown to be useful during PCA events when the lowest frequencies are not usable. Jull presented some alternate routing strategies that are not wholly pertinent to the current problem, but it did indicate the necessity for station diversity, a matter that was examined in the northern experiment [Goodman et al, 1997]. While Jull found discrepancies between model predictions and experimental data during disturbances, he did note that models are most useful during undisturbed periods.…”
Section: Earlier Communication Studiesmentioning
confidence: 99%